Expression and role of lumican in acute aortic dissection: A human and mouse study - Chen, Shao-Wei (PLoS One, 2021)
INTRODUCTION: Aortic dissection (AD) is a life-threatening emergency, and lumican (LUM) is a potential Biomarker for AD diagnosis. We investigated LUM expression patterns in patients with AD and explored the molecular functions of Lum in AD mice model. METHODS: LUM expression patterns were analyzed using aortic tissues of AD patients, and serum soluble LUM (s-LUM) levels were compared between patients with acute AD (AAD) and chronic AD (CAD). Lum-knockout (Lum(−/−)) mice were challenged with β-aminopropionitrile (BAPN) and angiotensin II (Ang II) to induce AD. The survival rate, AD incidence, and aortic aneurysm (AA) in these mice were compared with those in BAPN–Ang II–challenged wildtype (WT) mice. Tgf-β/Smad2, Mmps, Lum, and Nox expression patterns were examined. RESULTS: LUM expression was detected in the intima and media of the ascending aorta in patients with AAD. Serum s-LUM levels were significantly higher in patients with AAD than CAD. Furthermore, AD-associated mortality and thoracic aortic rupture incidence were significantly higher in the Lum(−/−) AD mice than in the WT AD mice. However, no significant pathologic changes in AA were observed in the Lum(−/−) AD mice compared with the WT AD mice. The BAPN–Ang II–challenged WT and Lum(−/−) AD mice had higher Tgf-β, p-Smad2, Mmp2, Mmp9, and Nox4 levels than those of non-AD mice. We also found that Lum expression was significantly higher in the BAPN-Ang II–challenged WT in comparison to the unchallenged WT mice. CONCLUSION: LUM expression was altered in patients with AD display increased s-LUM in blood, and Lum(−/−) mice exhibited augmented AD pathogenesis. These findings support the notion that LUM is a biomarker signifying the pathogenesis of injured aorta seen in AAD. The presence of LUM is essential for maintenance of connective tissue integrity. Future studies should elucidate the mechanisms underlying LUM association in aortic changes.